Pemetrexad in treating patients with locally advanced or metastatic lung adenocarcinoma - عبدالله نادر (Latakia University Journal -Medical Sciences Series, 2022)
Chemotherapy is the primary treatment in metastatic and locally advanced molecular biomarker negative non-small cell lung cancer. Platinum-based chemotherapy with a third-generation agent (gemcitabine, paclitaxel, docetaxel, or vinorelbine) has significantly improved median survival and quality of life in those patients Pemetrexed in combination with platinum based therapy has recently been considered the preferred first-line treatment option in locally advanced and metastatic non-squamous non-small cell lung cancers. The aim of this retrospective study was to evaluate the efficacy of pemetrexad in patients with locally advanced or metastatic lung adenocarcinoma in terms of recurrence-free survival. The study included 47 patients who attended the Chemotherapy and Radiotherapy Center from September 2018 to April 2021 who had locally advanced and metastatic lung adenocarcinoma. The average age of patients is 57.74 years, including 34 males and 13 females. The performance status of patients is between 0-2. 17 patients received treatment as a first line, 16 patients as a second line . and 14 patients as a third line. The combination with cisplatin was in 12 patients, with carboplatin 16 patients and 19 patients who received as monotherapy. The average recurrence-free survival rate, regardless of the treatment line, was 6.55 months (1-24 months). The response was better when it was used as a first line of treatment. The average relapse-free survival rate was 8.59 months compared to 6.56 months as a second line and 4,07 months as the third line with a statistically significant value p = 0,025 as well as the response was better in patients with good performance status 0-1 versus 2 9.86 months compared to 3.64 months with a statistically significant value p = 0.006.While there was no statistically significant difference in effectiveness according to drug combination, gender and smoking status. Pemetrexad in combination with platinum based therapy is considered the best treatment option in patients with locally advanced and metastatic lung adenocarcinoma, especially in patients with a good performance status PS=0-1.